Mitochondrial abundance and function in muscle from beef steers with divergent residual feed intakes - E.E. Fernandez; J.W. Oltjen; R.D. Sainz (Animal, 2020)
The objective of this study was to evaluate the relationship between muscle mitochondrial function and residual feed intake (RFI) in growing beef cattle. A 56-day feeding trial was conducted with 81 Angus × Hereford steers (initial BW = 378 ± 43 kg) from the University of California Sierra Foothills Research Station (Browns Valley, CA, USA). All steers were individually fed the same finishing ration (metabolizable energy = 3.28 Mcal/kg DM). Average daily gain (ADG), DM intake (DMI) and RFI were 1.82 ± 0.27, 8.89 ± 1.06 and 0.00 ± 0.55 kg/day, respectively. After the feeding trial, the steers were categorized into high, medium and low RFI groups. Low RFI steers consumed 13.6% less DM (P < 0.05) and had a 14.1% higher G : F ratio (P < 0.05) than the high RFI group. No differences between RFI groups were found in age, ADG or BW (P > 0.10). The most extreme individuals from the low and high RFI groups were selected to assess mitochondrial function (n = 5 low RFI and n = 6 high RFI). Mitochondrial respiration was measured using an oxygraph (Hansatech Instruments Ltd., Norfolk, UK). State 3 and State 4 respiration rates were similar between both groups (P > 0.10). Respiratory control ratios (RCRs, i.e., State 3 : State 4 oxygen uptakes) declined with animal age and were greater in low RFI steers (4.90) as compared to high RFI steers (4.26) when adjusted for age by analysis of covariance (P = 0.003). Mitochondrial complex II activity levels per gram of muscle were 42% greater in low RFI steers than in high RFI steers (P = 0.004). These data suggest that skeletal muscle mitochondria have greater reserve respiratory capacity and show greater coupling between respiration and phosphorylation in low RFI than in high RFI steers.